2020
DOI: 10.1186/s12934-020-01466-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite secretions of Lactobacillus plantarum YYC-3 may inhibit colon cancer cell metastasis by suppressing the VEGF-MMP2/9 signaling pathway

Abstract: Background Colorectal cancer (CRC) is a major clinical challenge, and the gut microbiome plays important roles in the occurrence and metastasis of CRC. Lactobacillus and their metabolites are thought to be able to suppress the growth of CRC cells. However, the antimetastatic mechanism of Lactobacillus or their metabolites toward CRC cells is not clear. Therefore, the aim of this study was to assess the inhibitory mechanism of cell-free supernatants (CFSs) of L. rhamnosus GG, L. casei M3, and L. plantarum YYC-3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 41 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…They showed that pre-inoculation with L. acidophilus in Bulb/c mice resulted in retarding tumor volume growth, lowered histopathology scores, enhanced apoptosis of tumor cells, and down-regulated surface proteins' expression 25 . Besides, Yue et al found that the metabolites of L. acidophilus could suppress the cell metastasis of colon cancer by inhibiting the VEGF/MMPs signaling pathway 28 . Agah et al showed that L. acidophilus could induce a lower level of CEA and CA19-9 and a higher level of IFN-γ in the azoxymethane-induced colon cancer by altering the T-Cell signature to increase CD4+ and CD8+ cells 10 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…They showed that pre-inoculation with L. acidophilus in Bulb/c mice resulted in retarding tumor volume growth, lowered histopathology scores, enhanced apoptosis of tumor cells, and down-regulated surface proteins' expression 25 . Besides, Yue et al found that the metabolites of L. acidophilus could suppress the cell metastasis of colon cancer by inhibiting the VEGF/MMPs signaling pathway 28 . Agah et al showed that L. acidophilus could induce a lower level of CEA and CA19-9 and a higher level of IFN-γ in the azoxymethane-induced colon cancer by altering the T-Cell signature to increase CD4+ and CD8+ cells 10 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Animal gut microbiota is one of the largest and most complicated existing micro-ecosystems that provides an important barrier to bacterial infections ( Lynch and Pedersen, 2016 ; Li et al., 2020 ; Liu et al., 2020b ). Additionally, it helps in providing mucosal immunity, material metabolism, and nutrient absorption and regulation ( Wu and Wu, 2012 ; Yue et al., 2020 ). Generally, ongoing competition and interaction of microorganisms may gradually change in microbial community structure from simple to a complicated and eventually a dynamic and balanced ecosystem ( Jami et al., 2013 ; Zhao et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of the PFM are the most often given as a percentage or mg/mL, less often in µg/mL. The range of the tested concentrations is from 0.47% to 100% [ 11 , 35 , 36 , 37 , 38 , 39 ] or from 0.0001 to 1000 mg/mL [ 18 , 29 , 31 , 34 , 40 , 41 ]. In all of the above-mentioned studies, the MTT assay dominates as a tool of antiproliferative activity testing for cancerous cell lines and cytotoxicity assayed to normal cells.…”
Section: Resultsmentioning
confidence: 99%